A formação territorial da cidade de Xanxerê, SC - Tombini, Débora Aparecida (2015)
In this paper we analyzed the territorial formation of the city of Xanxerê since its foundation in 1954 mainly from the 1970s until today, trying to identify the main transforming social agents and the aspiration of the population nowadays. The methodology used is based on bibliographical research in order to understand the formation of the city, data raising through field work applying questionnaires and interviews to identify the main social agents that act in the territorial formation, the mechanisms used and aspiration of the population. As a result it was identified the social groups of the city of Xanxere, real estate agents, landing owners, government, entrepreneurs and population of the districts. The real estate agents develop actions in the process of expansion and organization of the city doing several operations such as financing, administration and commercialization; the land owners act in the territorial formation when they share the land to profit; the government is responsible to approve the projects and land development as well as the territorial formation creating laws the surround the city, alteration of laws and investment in infrastructure serving the interests of businessmen in the civil construction; businessmen that claim improvement in the infrastructure and to create more jobs and better salaries; the citizens act in search of a better life. This research also showed aspirations of the population in the districts Colatto, Primo Tacca, Matinho and Vila União about services and equipment. These aspirations are related to increase/construction of Municipal centers to young kids, construction of health units, pavement and illumination of streets. The residents of the irregular land in development required the legalization of their houses or support to move to a safer area. These aspirations reflect the deficiency of equipment and services that could and should be available in order to offer a better life quality to the people of the city.